SLEEP QUALITY AND FUNCTIONAL STATUS ON POST-STROKE PATIENTS - anis ika nur rohmah (POLTEKKES KEMENKES YOGYAKARTA, 2021)
Stroke is a condition in which the brain function has stops working due to interference by the circulation of oxygen in the blood into the parts of the brain. The emergence of disability and weakness of motor function as a result of stroke affects the functional status of patients after stroke. Another problem that is often encountered by post-stroke patients is sleep disturbance. The purpose of this study was to determine the relationship between sleep quality and the functional status of post-stroke patients. The type of research conducted in this study is an analytic study with a cross-sectional approach. Post-stroke patients who underwent the treatment in the outpatient unit of Wava Husada Hospital were the population in this study. The sample in this study was determined as many as 84 respondents using the GPower application. Measurement of sleep quality using the PSQI questionnaire and functional status using FIM. Data analysis using Pearson Correlation test. The results showed that 82,1% of respondents had poor sleep quality. 78,6% of respondents in the functional status category were relatively dependent on assistance. Pearson Correlation analysis results obtained p-value = 0,000 (<? = 0,05) with a degree of relationship of 0,720. These results indicate that there is a strong relationship between sleep quality and functional status in post-stroke patients. It is suggested to the nursing profession to improve sleep quality on post-stroke patients to accelerate the improvement of functional status on patients.